Wear-resistant high-entropy alloy composite protective coating and preparation method thereof
By using supersonic flame spraying technology to deposit WC-CrNbMoTaZr coating on aviation structural parts, and combining glow ion sulfur permeability technology to form sulfur permeability, the environmental pollution and human health hazards of the existing electrochromic plating process are solved, and a composite protective coating with high wear resistance and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411597005.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-04-22
AI Technical Summary
The existing electrochromium plating process has environmental pollution, hydrogen embrittlement problems and potential harm to human health, making it difficult to ensure the safety and life of aviation structural parts.
Supersonic flame spraying technology is used to deposit WC-CrNbMoTaZr coating on the surface of the metal parts matrix, and a sulfur permeability layer is formed through glow ion sulfur permeability technology to prepare a wear-resistant high-entropy alloy composite protective coating.
It improves the bonding force between the coating and the substrate, enhances the wear resistance and corrosion resistance of the coating, reduces the risk of coating peeling, and avoids environmental pollution and human health hazards of the electroplating process.
Smart Images

Figure CN119859782A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material surface coating, and in particular to a wear-resistant high-entropy alloy composite protective coating and a preparation method thereof. Background Art
[0002] Aircraft landing gear and other aviation structural parts are generally made of high-strength steel or titanium alloy. In order to cooperate with the surface protection of parts, electroplating is widely used for surface treatment. Due to the characteristics of chrome plating or chrome-titanium surface treatment process: it is easy to cause environmental pollution during the manufacturing process, and the parts have potential problems such as hydrogen embrittlement, which cannot well guarantee the safety and life of aviation structural parts such as landing gear; at the same time, this process is recognized to be harmful to human health. Therefore, it is crucial to develop a technology to replace the electroplating chromium process, whether for environmental protection needs, economic needs or humanistic care needs. Compared with ordinary electroplating process, supersonic flame spraying process has the advantages of low equipment investment cost, simple and convenient construction process, and no environmental pollution. It is considered to be the most likely process to replace electroplating hard chrome. At the same time, high entropy alloy coating has outstanding advantages in improving wear resistance and this type of coating has excellent properties such as high hardness and high corrosion resistance. Summary of the invention
[0003] The technical problem solved by the present invention is to provide a wear-resistant high-entropy alloy composite protective coating and a preparation method thereof to solve the problems in the above-mentioned background technology.
[0004] The technical problem solved by the present invention is achieved by adopting the following technical solutions: A wear-resistant high-entropy alloy composite protective coating is applied to a metal part substrate, comprising a WC-CrNbMoTaZr coating and a sulfurized layer, wherein the surface of the metal part substrate is pre-treated by laser engraving and then the WC-CrNbMoTaZr coating is deposited, and then the WC-CrNbMoTaZr coating is sulfurized by glow ion sulfurization technology to obtain the sulfurized layer.
[0005] In the present invention, the thickness of the WC-CrNbMoTaZr coating is 40-200 μm, wherein the mass fraction of WC is 50-90%, and the atomic proportions of Cr, Nb, Mo, Ta, and Zr elements in the high entropy alloy are close; the thickness of the sulfurized layer is 10-20 μm.
[0006] A method for preparing a wear-resistant high-entropy alloy composite protective coating, the specific steps are as follows: Step 1) First, the surface of the metal part substrate is degreased and then sandblasted; Step 2) The dried metal part substrate is mounted on a sample stage, and a structure is engraved on the surface of the metal part substrate by a fiber laser in a vacuum chamber; Step 3) using supersonic flame spraying technology to deposit a WC-CrNbMoTaZr coating on the surface of the engraved metal part substrate; Step 4) using glow ion sulfurizing technology, performing sulfurizing treatment on the surface of the deposited WC-CrNbMoTaZr coating to obtain a sulfurized layer; Step 5) After the temperature of the vacuum chamber drops to room temperature, the vacuum chamber is opened and the metal part substrate is taken out. The coating obtained on the surface of the metal part substrate is a composite protective coating having a WC-CrNbMoTaZr coating + a sulfurized layer.
[0007] In the present invention, in step (2), the fiber laser has a 1064 nm laser beam, the laser power is controlled to be 10-20 W, the pulse repetition frequency is 20 kHz, and the marking speed is 10-30 mm s -1 The engraved structure has a depth of 10~15 μm, a width of 5~10 μm, and a hexagonal mesh path with a side length of 2.5 mm.
[0008] In the present invention, in step (3), the WC-CrNbMoTaZr coating deposition process parameters are: kerosene flow rate 5.8~6.5GPH, oxygen flow rate 1850~2100SCFH, powder delivery carrier gas 20~25SCFH, powder delivery speed 5~10RPM, spraying distance 350~400mm.
[0009] In the present invention, in step (4), the process parameters for the sulfurization treatment of the sulfurized layer are: the sulfurization temperature is 450-650°C, the working gas is high-purity CS2 (purity>99.999%), the gas flow is controlled by the gas pressure, the pressure is 20-40Pa, and the sulfurization time is 3-8 hours. Beneficial Effects
[0010] 1) The present invention performs laser engraving pretreatment on the metal part substrate before coating with the wear-resistant high-entropy alloy composite protective coating. Compared with spraying directly on the surface of the smooth metal part substrate, the substrate-coating bonding strength is significantly improved, and the risk of coating peeling failure is effectively reduced; 2) The WC-CrNbMoTaZr coating of the present invention adopts supersonic flame spraying technology, which effectively solves the problem of insufficient hardness and wear resistance of the Cr coating itself by electroplating. At the same time, the process technology is mature, low-cost and basically does not cause harm to the environment and human health; 3) The present invention uses CS2 gas source to perform sulfurization treatment to obtain a sulfurized layer. At the same time, the ratio of sulfide and carbide can be regulated by the sulfurization reaction temperature and reaction pressure, thereby regulating the surface hardness of the sulfurized layer. An ideal composite protective coating consisting of a WC-CrNbMoTaZr metal ceramic coating and a sulfurized layer with a low surface friction coefficient is formed on the surface of a metal part substrate with low hardness. The coating has good corrosion resistance and is suitable for use in various environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a schematic plan view of the engraving structure prepared on the surface of the metal part substrate in an embodiment of the present invention.
[0012] Figure 2 This is a schematic diagram of the change in friction curves of high-strength steel and high-strength steel with a wear-resistant high-entropy alloy composite protective coating under 5kg load conditions in Example 1 of the present invention.
[0013] Figure 3 This is a schematic diagram of the change in friction curves of high-strength steel and high-strength steel with a wear-resistant high-entropy alloy composite protective coating under 5kg load conditions in Example 2 of the present invention.
[0014] Figure 4 This is a schematic diagram of the change in friction curves of high-strength steel and high-strength steel with wear-resistant high-entropy alloy composite protective coating under 5kg load conditions in Example 3 of the present invention. DETAILED DESCRIPTION
[0015] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0016] A wear-resistant high-entropy alloy composite protective coating comprises a metal part substrate, a WC-CrNbMoTaZr coating and a sulfurized layer, wherein the WC-CrNbMoTaZr coating is deposited on the surface of the metal part substrate after laser engraving, and then the WC-CrNbMoTaZr coating is sulfurized by glow ion sulfurization technology to obtain the sulfurized layer; the WC-CrNbMoTaZr coating has a thickness of 40-200 μm, a WC mass fraction of 50-90%, and the atomic proportions of Cr, Nb, Mo, Ta and Zr elements in the high-entropy alloy are close; and the sulfurized layer has a thickness of 10-20 μm. Example 1
[0017] A method for preparing a wear-resistant high-entropy alloy composite protective coating, the specific steps are as follows: Step 1) First, the surface of the metal part substrate is degreased using an organic solvent such as alcohol or acetone, and then sandblasted; Step 2) The dried metal part substrate is mounted on the sample stage. In the vacuum chamber, a fiber laser is used to engrave a structure on the surface of the metal part substrate. The fiber laser has a 1064 nm laser beam, a laser power control of 10-20 W, a pulse repetition frequency of 20 kHz, and a marking speed of 10-30 mm s. -1 The engraved structure has a depth of 10-15 μm, a width of 5-10 μm, and a hexagonal mesh path with a side length of 2.5 mm. Step 3) using supersonic flame spraying technology to deposit a WC-CrNbMoTaZr coating on the surface of the engraved metal part substrate, the kerosene flow rate during spraying is 5.8~6.5GPH, the oxygen flow rate is 1850~2100SCFH, the powder carrier gas is 20~25SCFH, the powder feeding speed is 5~10RPM, and the spraying distance is 350~400mm; the thickness of the WC-CrNbMoTaZr coating is 150μm, the mass fraction of WC in the WC-CrNbMoTaZr coating is 50%, the mass fraction of the high entropy alloy is 50%, and the atomic proportions of the Cr, Nb, Mo, Ta, and Zr elements in the high entropy alloy are close; Step 4) using glow ion sulfurizing technology, the surface of the deposited WC-CrNbMoTaZr coating is sulfurized, the sulfurizing temperature is 500°C, the working gas is high-purity CS2 (purity>99.999%), the gas flow is controlled by the gas pressure, the pressure is 28Pa, the sulfurizing time is 4 hours, and the thickness of the sulfurized layer is 11μm; Step 5) After the temperature of the vacuum chamber drops to room temperature, the vacuum chamber is opened and the metal part substrate is taken out. The coating obtained on the surface of the metal part substrate is a composite protective coating having a WC-CrNbMoTaZr coating + a sulfurized layer.
[0018] The performance of the wear-resistant high entropy alloy composite protective coating prepared in Example 1 was tested. Figure 2 The figure shows the change of friction curve of high-strength steel and high-strength steel with wear-resistant high-entropy alloy composite protective coating under 5kg load conditions. The hardness of high-strength steel is about 300HV. After coating with wear-resistant high-entropy alloy composite protective coating, the hardness is increased to 1000HV. The friction coefficients of high-strength steel and high-strength steel with wear-resistant high-entropy alloy composite protective coating are 0.34 and 0.29 respectively. It can be seen that the material hardness and wear resistance are significantly improved after coating with wear-resistant high-entropy alloy composite protective coating. Example 2
[0019] A method for preparing a wear-resistant high-entropy alloy composite protective coating, the specific steps are as follows: Step 1) First, the surface of the metal part substrate is degreased using an organic solvent such as alcohol or acetone, and then sandblasted; Step 2) The dried metal part substrate is mounted on the sample stage. In the vacuum chamber, a fiber laser is used to engrave a structure on the surface of the metal part substrate. The fiber laser has a 1064 nm laser beam, a laser power control of 10-20 W, a pulse repetition frequency of 20 kHz, and a marking speed of 10-30 mm s. -1 The engraved structure has a depth of 10-15 μm, a width of 5-10 μm, and a hexagonal mesh path with a side length of 2.5 mm. Step 3) using supersonic flame spraying technology to deposit a WC-CrNbMoTaZr coating on the surface of the engraved metal part substrate, the kerosene flow rate during spraying is 5.8~6.5GPH, the oxygen flow rate is 1850~2100SCFH, the powder carrier gas is 20~25SCFH, the powder feeding speed is 5~10RPM, and the spraying distance is 350~400mm; the thickness of the WC-CrNbMoTaZr coating is 150μm, the mass fraction of WC in the WC-CrNbMoTaZr coating is 65%, the mass fraction of the high entropy alloy is 35%, and the atomic proportions of the Cr, Nb, Mo, Ta, and Zr elements in the high entropy alloy are close; Step 4) using glow ion sulfurizing technology, the surface of the deposited WC-CrNbMoTaZr coating is sulfurized, the sulfurizing temperature is 550°C, the working gas is high-purity CS2 (purity>99.999%), the gas flow is controlled by the gas pressure, the pressure is 32Pa, the sulfurizing time is 6 hours, and the thickness of the sulfurized layer is 15μm; Step 5) After the temperature of the vacuum chamber drops to room temperature, the vacuum chamber is opened and the metal part substrate is taken out. The coating obtained on the surface of the metal part substrate is a composite protective coating having a WC-CrNbMoTaZr coating + a sulfurized layer.
[0020] The performance of the wear-resistant high entropy alloy composite protective coating prepared in Example 2 was tested. Figure 3 The figure shows the change of friction curve of high-strength steel and high-strength steel with wear-resistant high-entropy alloy composite protective coating under 5kg load conditions. The hardness of high-strength steel is about 300HV. After coating with wear-resistant high-entropy alloy composite protective coating, the hardness is increased to 1000HV. The friction coefficients of high-strength steel and high-strength steel with wear-resistant high-entropy alloy composite protective coating are 0.34 and 0.3 respectively. It can be seen that the material hardness and wear resistance are significantly improved after coating with wear-resistant high-entropy alloy composite protective coating. Example 3
[0021] A method for preparing a wear-resistant high-entropy alloy composite protective coating, the specific steps are as follows: Step 1) First, the surface of the metal part substrate is degreased using an organic solvent such as alcohol or acetone, and then sandblasted; Step 2) The dried metal part substrate is mounted on the sample stage. In the vacuum chamber, a fiber laser is used to engrave a structure on the surface of the metal part substrate. The fiber laser has a 1064 nm laser beam, a laser power control of 10-20 W, a pulse repetition frequency of 20 kHz, and a marking speed of 10-30 mm s -1 The engraved structure has a depth of 10-15 μm, a width of 5-10 μm, and a hexagonal mesh path with a side length of 2.5 mm. Step 3) using supersonic flame spraying technology to deposit a WC-CrNbMoTaZr coating on the surface of the engraved metal part substrate, the kerosene flow rate during spraying is 5.8~6.5GPH, the oxygen flow rate is 1850~2100SCFH, the powder carrier gas is 20~25SCFH, the powder feeding speed is 5~10RPM, and the spraying distance is 350~400mm; the thickness of the WC-CrNbMoTaZr coating is 150μm, the mass fraction of WC in the WC-CrNbMoTaZr coating is 65%, the mass fraction of the high entropy alloy is 35%, and the atomic proportions of the Cr, Nb, Mo, Ta, and Zr elements in the high entropy alloy are close; Step 4) using glow ion sulfurizing technology, the surface of the deposited WC-CrNbMoTaZr coating is sulfurized, the sulfurizing temperature is 550°C, the working gas is high-purity CS2 (purity>99.999%), the gas flow is controlled by the gas pressure, the pressure is 30Pa, the sulfurizing time is 4 hours, and the thickness of the sulfurized layer is 12μm; Step 5) After the temperature of the vacuum chamber drops to room temperature, the vacuum chamber is opened and the metal part substrate is taken out. The coating obtained on the surface of the metal part substrate is a composite protective coating having a WC-CrNbMoTaZr coating + a sulfurized layer.
[0022] The performance of the wear-resistant high entropy alloy composite protective coating prepared in Example 3 was tested. Figure 4 The figure shows the change of friction curve of high-strength steel and high-strength steel with wear-resistant high-entropy alloy composite protective coating under 5kg load conditions. The hardness of high-strength steel is about 300HV. After coating with wear-resistant high-entropy alloy composite protective coating, the hardness is increased to 1100HV. The friction coefficients of high-strength steel and high-strength steel with wear-resistant high-entropy alloy composite protective coating are 0.34 and 0.32 respectively. It can be seen that the material hardness and wear resistance are significantly improved after coating with wear-resistant high-entropy alloy composite protective coating.
[0023] exist Figure 1 P in the middle is the carving path; Figure 2~Figure 4 In the figure, steel is high-strength steel, and WC is high-strength steel coated with a wear-resistant high-entropy alloy composite protective coating.
[0024] In the above-mentioned Examples 1 to 3, the metal part substrate is pre-treated by laser engraving before coating with the wear-resistant high-entropy alloy composite protective coating. Compared with spraying directly on the surface of the smooth metal part substrate, the substrate-coating bonding strength is significantly improved, and the risk of peeling and failure of the coating is effectively reduced.
[0025] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A wear-resistant high-entropy alloy composite protective coating, characterized in that: The invention is applied to a metal part substrate, comprising a WC-CrNbMoTaZr coating and a sulfurized layer, wherein the surface of the metal part substrate is pre-treated by laser engraving and then the WC-CrNbMoTaZr coating is deposited, and then the WC-CrNbMoTaZr coating is sulfurized by glow ion sulfurization technology to obtain the sulfurized layer.
2. The wear-resistant high-entropy alloy composite protective coating according to claim 1, characterized in that: The WC-CrNbMoTaZr coating has a thickness of 40-200 μm, wherein the mass fraction of WC is 50-90%, and the atomic proportions of Cr, Nb, Mo, Ta, and Zr elements in the high entropy alloy are close.
3. The wear-resistant high-entropy alloy composite protective coating according to claim 1, characterized in that: The thickness of the sulfurized layer is 10-20 μm.
4. A method for preparing a wear-resistant high-entropy alloy composite protective coating, preparing the wear-resistant high-entropy alloy composite protective coating as described in any one of claims 1 to 3, characterized in that: The specific steps are as follows: Step 1) First, the surface of the metal part substrate is degreased and then sandblasted; Step 2) The dried metal part substrate is mounted on a sample stage, and a structure is engraved on the surface of the metal part substrate by a fiber laser in a vacuum chamber; Step 3) using supersonic flame spraying technology to deposit a WC-CrNbMoTaZr coating on the surface of the engraved metal part substrate; Step 4) using glow ion sulfurizing technology, performing sulfurizing treatment on the surface of the deposited WC-CrNbMoTaZr coating to obtain a sulfurized layer; Step 5) After the temperature of the vacuum chamber drops to room temperature, the vacuum chamber is opened and the metal part substrate is taken out. The coating obtained on the surface of the metal part substrate is a composite protective coating having a WC-CrNbMoTaZr coating + a sulfurized layer.
5. The method for preparing a wear-resistant high-entropy alloy composite protective coating according to claim 4, characterized in that: In step (2), the fiber laser has a 1064 nm laser beam, the laser power is controlled to be 10-20 W, the pulse repetition frequency is 20 kHz, and the marking speed is 10-30 mm s -1 .
6. The method for preparing a wear-resistant high-entropy alloy composite protective coating according to claim 4, characterized in that: In step (2), the engraved structure has a depth of 10-15 μm, a width of 5-10 μm, and a hexagonal mesh path with a side length of 2.5 mm.
7. The method for preparing a wear-resistant high-entropy alloy composite protective coating according to claim 4, characterized in that: In step (3), the WC-CrNbMoTaZr coating deposition process parameters are: kerosene flow rate 5.8~6.5GPH, oxygen flow rate 1850~2100SCFH, powder delivery carrier gas 20~25SCFH, powder delivery speed 5~10RPM, spraying distance 350~400mm.
8. The method for preparing a wear-resistant high-entropy alloy composite protective coating according to claim 4, characterized in that: In step (4), the process parameters for the sulfurization treatment of the sulfurized layer are: the sulfurization temperature is 450-650°C, the working gas is high-purity CS2 (purity>99.999%), the pressure is 20-40Pa, and the sulfurization time is 3-8 hours.
Citation Information
Patent Citations
Process for spraying composite coating on metal surface
CN104789921A
High entropy alloy with antifriction and wear resistance
CN109252162A
Preparation method of high-entropy ceramic composite coating
CN111254376A
Method for preparing high-entropy coating for high-speed rail bearing through laser cladding
CN117144353A